PREVENTING LAND MAFIA USING POSITIVE LAND REGISTRY SYSTEM - Bambang Sulistyo Widjanarko (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Registration of land nowadays is in the form of publication from negative toward positive, meaning land certificate as the strongest proof of legal ownership still can be aborted by other parties who could provide stronger legitimate proves of ownership. The main problem is that the data that being used as basic of land registration is out date, never been upgrade and in less orderly administration. The land parcel data is kept and being held secretly by the village head and government official. This disorder condition is being used by the land mafia and the corrupted official to their advantages. Such conditions are very disadvantages for landowners because there is no legal certainty and justice resulted in land disputes. In many cases, double land certificate occurred. As a final result it is hard for the government to do land acquisitions for country development. The solution for this problem is by doing a positive land registry system. This system will obtain the real accurate data parcel in the field. To be able to provide an accurate updated data, it is must be done by empower cooperation between governmental village administration, village official and villagers themselves. All plots of land boundary in the village is marked and mapped by shareholders, recorded, verified, announced and later be approved as the real data parcel plotted by villager (contradiktur delimitation). All of the process supervised by the government land officials that later can be legalized by the court. This positive land registration system gives strongest complete evidences that cannot be overturned by a judge in the court. Keywords : Preventing, Land Mafia, Positive Land, Registry System.